FAKTOR YANG MEMPENGARUHI KEJADIAN INFERTILITAS PADA WANITA USIA SUBUR DI RSIA FAJAR WIROBRAJAN, PATANGPULUHAN, YOGYAKARTA - Isna Yuswella Babys (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Infertility is inability to get pregnant after 12 months or 6 months in women over 35 years old without using contraception and having active sexual intercourse. The World Health Organization (WHO) states that out of every 6 people, 1 of them experiences infertility. Of the 237 million people in Indonesia, there are 39.8 million women of childbearing age, but seven to eight million of them are considered infertile. Based on a preliminary study at Maternal and Child Hospital  “Fajar”, there were 103 infertile female patients who were examined in January - March 2021. Objective: This research is aimed identifying factors affecting infertility in women of childbearing age at Maternal and Child Hospital “Fajar”, Wirobrajan, Patangpuluhan, Yogyakarta. Methods: This research was conducted at Maternal and Child Hospital “Fajar”. It is an analytical research with cross sectional design. The population was 103 infertile women who were examined from January to March 2021 with a sample size of 32 infertile women based on the criteria. The samples were taken using total sampling. Univariate and bivariate statistical tests employed Fisher’s Exact test, which is an alternative to Chi Square test. Results: The results of univariate analysis indicated that infertility in the non-risk group was 43.8%, abnormal nutritional status was 56.2%. Irreguler menstrual cycle was 79.9%,  had primary infertility by  96.9%. The results of bivariate indicated that  age (p = 0.037), nutritional status (p = 0.007), menstrual cycle (p = 0.004). Conclusion: There is an influence of nutritional status, and menstrual cycle on infertility in women of childbearing age.